Lsi2: A black box in plant silicon transport - Coskun, Devrim; Deshmukh, Rupesh; Shivaraj, S. M.; Isenring, Paul; Belanger, Richard R. (Plant and Soil, 2021)
Background Silicon (Si) is widely considered a non-essential but beneficial element for higher plants, providing broad protection against various environmental stresses (both biotic and abiotic), particularly in species that can readily absorb the element. Two plasma-membrane proteins are known to coordinate the radial transport of Si (in the form of Si(OH)(4)) from soil to xylem within roots: the influx channel Lsi1 and the efflux transporter Lsi2. From a structural and mechanistic perspective, much more is known about Lsi1 (a member of the NIP-III subgroup of the Major Intrinsic Proteins) compared to Lsi2 (a putative Si(OH)(4)/H+ antiporter, with some homology to bacterial anion transporters). Scope Here, we critically review the current state of understanding regarding the physiological role and molecular characteristics of Lsi2. We demonstrate that the structure-function relationship of Lsi2 is largely uncharted and that the standing transport model requires much better supportive evidence. We also provide (to our knowledge) the most current and extensive phylogenetic analysis of Lsi2 from all fully sequenced higher-plant genomes. We end by suggesting research directions and hypotheses to elucidate the properties of Lsi2. Conclusions Given that Lsi2 is proposed to mediate xylem Si loading and thus root-to-shoot translocation and biosilicification, it is imperative that the field of Si transport focus its efforts on a better understanding of this important topic. With this review, we aim to stimulate and advance research in the field of Si transport and thus better exploit Si to improve crop resilience and agricultural output.
Keywords: Efflux; Lsi2; Membrane transport; Root-to-shoot translocation; silicon; Xylem loading

Speed breeding opportunities and challenges for crop improvement - Sharma, Shivani; Kumar, Amit; Dhakte, Priyanka; Raturi, Gaurav; Vishwakarma, Gautam; Barbadikar, Kalyani M.; Das, B. K.; Shivaraj, S. M.; Sonah, Humira; Deshmukh, Rupesh (Journal of Plant Growth Regulation, 2023)
Crop improvement in light of the rapidly changing climate and the increasing human population continues to be one of the primary concerns for researchers across the globe. The rate at which current crop improvement programs are progressing is essentially inadequate to meet the food demand. There is an urgent need for redesigning the crops for climate resilience and sustainable yield and nutrition. The rate of crop improvement is largely impeded owing to the long generation time taken by crop plants during the breeding process. As a solution in this direction, speed breeding is now being practiced at a large scale to reduce generation time to accommodate multiple generations of crops per year. To enhance the efficiency of breeding, researchers are now adopting an integrated approach where speed breeding is used along with modern plant breeding and genetic engineering technologies. In the present review, we have summarized the technological aspects, opportunities, and limitations associated with speed breeding. The application of speed breeding such as mapping population development, haplotype-based breeding, transgenic breeding, and genome-edited line advancement has also been discussed. Speed breeding is a promising technology that expedites the goals of food and industrial crop improvement by reducing the breeding cycles for establishing nutritional security and sustainable agriculture.
Keywords: Genome editing; Genomic selection; Haplotype breeding; Speed breeding; Transgenic breeding